Detection of respiratory viruses and Bordetella bronchiseptica in dogs with acute respiratory tract infections - Schulz, B.S. (Vet J, 2014)
Canine infectious respiratory disease (CIRD) is an acute, highly contagious disease complex caused by a variety of infectious agents. At present, the role of viral and bacterial components as primary or secondary pathogens in CIRD is not fully understood. The aim of this study was to investigate the prevalence of canine parainfluenza virus (CPIV), canine adenovirus type 2 (CAV-2), canine influenza virus (CIV), canine respiratory coronavirus (CRCoV), canine herpes virus-1 (CHV-1), canine distemper virus (CDV) and Bordetella bronchiseptica in dogs with CIRD and to compare the data with findings in healthy dogs. Sixty-one dogs with CIRD and 90 clinically healthy dogs from Southern Germany were prospectively enrolled in this study. Nasal and pharyngeal swabs were collected from all dogs and were analysed for CPIV, CAV-2, CIV, CRCoV, CHV-1, CDV, and B. bronchiseptica by real-time PCR. In dogs with acute respiratory signs, 37.7% tested positive for CPIV, 9.8% for CRCoV and 78.7% for B. bronchiseptica. Co-infections with more than one agent were detected in 47.9% of B. bronchiseptica-positive, 82.6% of CPIV-positive, and 100% of CRCoV-positive dogs. In clinically healthy dogs, 1.1% tested positive for CAV-2, 7.8% for CPIV and 45.6% for B. bronchiseptica. CPIV and B. bronchiseptica were detected significantly more often in dogs with CIRD than in clinically healthy dogs (P < 0.001 for each pathogen) and were the most common infectious agents in dogs with CIRD in Southern Germany. Mixed infections with several pathogens were common. In conclusion, clinically healthy dogs can carry respiratory pathogens and could act as sources of infection for susceptible dogs.